Effects of Self-Efficacy Promoting Program through Family Participation upon Food Consumption Knowledge and Nutritional Status among Upper-Primary School Underweight Muslim Children, Pattani Province: A Pilot study - Waloh, Waenurmee; Perngmark, Pajongsil; Boonyasopun, Umaporn (Princess of Naradhiwas University Journal, 2023)
The purpose of this pilot study was to study the effects of self-efficacy promoting program through family participation upon food consumption knowledge and nutritional status among upper-primary school underweight Muslim children. The samples consisted of 10 underweight Muslim children, selected by purposive sampling. The group participated in the self-efficacy promoting program. Data were collected through the self-efficacy in food consumption questionnaire (SeQ), the food behavior questionnaire (FbQ) of the school - aged children, and the family participation questionnaire (FpQ). The instruments were validated its contents by 3 experts. The instruments received Cronbach’s alpha yielding at 0.87, 0.83, and 0.75, respectively. The FkQ was tested using Kuder - Richardson 20 (KR - 20) yielding at 0.85. Descriptive statistics including frequency, percentage, mean, standard deviation and t-test were used to analyze data. The results revealed that after participation in the program, the mean scores of self-efficacy (Se), food consumption knowledge (Fk), and food behavior (Fb) the underweight Muslim children were significantly greater than before participating in the program with a statistical significance at .05 p < 0.01. However, the body weight of the children before and after participation in the program were not different. In conclusion, according to the study results, the program was able to increase self – efficacy of students in food consumption, which it can be implemented in schools aiming to change students’ food consumption behaviors and to help improve their weight.